Management of Personal Information among Library Staff at the University of Dar es Salaam, Tanzania - Mkhai, Emmanuel; Rashid, Nakivona Hashim (University of Dar es Salaam Library Journal, 2022)
Effective management of personal information is pivotal for its sustainable use. This article presents a study that has assessed the personal information management (PIM) practices of library staff at the University of Dar es Salaam (UDSM). The study used a descriptive research design deploying both qualitative and quantitative approaches under which questionnaire and focus group discussion guide were used to collect data. While qualitative data were subjected to content analysis, statistical analysis was used to generate descriptive and inferential statistics from quantitative data using IBM SPSS version 23. The findings have revealed that librarians at are generally aware of various PIM practices and use them to manage their personal information. The librarians use both physical and electronic tools to manage their personal information. These tools include physical folders, files, and boxes, which are used to manage physical information, and Dropbox, Google Drive, and iCloud which are used to manage electronic information. Several factors influence the effectiveness of librarians ' PIM practices. These include librarians ' demographic characteristics (age and levels of education), knowledge of the information cycle, information management skills, and available information systems. Factors such as inadequate information management skills and shortage of time have been found to undermine the effectiveness of the studied population ' s PIM practices. The study concludes that understanding factors that influence and undermine effective PIM practices is essential in setting a foundation for improving personal information management